Pengaruh Sosial, Materialisme, dan Impulse Buying terhadap Niat Membeli - Sari, Ni Ketut Alfita; Prianthara, Ida Bagus Teddy (Universitas Batanghari Jambi, 2024)
This research investigates how social influence, materialism, impulse buying, and purchase intentions relate to each other. This research data collection method uses the Google Forms platform. Herbalife customers in the Gianyar district receive questionnaires directly through QR codes and links. This study uses the semantic differential scale 1 (Very Disagree) – 10 (Absolutely agree). Besides, attitudes can also be measured on this scale; however, rather than double options or checklists, the shape is a continuum line. Furthermore, the structural equation model (SEM) is used with the SmartPLS (Partial Least Square) 4 version for data analysis. The results of the research hypothesis sample test showed that based on 105 responses social influence does not affect purchase intention. Materialism and impulsive buying affect purchase intention. Social influence and materialism affect impulsive buying.